Income Analysis of Maize Farmers Under the Contract Farming Scheme in Pamekasan, Indonesia - Mardiyah Hayati; Mohammad Wahyu Firdaus; Taufik Rizal Dwi Adi Nugroho; Desi Ramadhani; Fatahullah Fatahullah (Indonesian Journal of Sustainable Agriculture and Environmental Sciences (IJSAES), 2025)
Background: The contract farming system was chosen due to its potential to provide market certainty, access to agricultural inputs, and technical training for farmers. Aim: This study aims to analyze the cost components and income of maize farming conducted under the contract farming scheme in Pamekasan Regency.  Methods: The research was conducted in Kadur District and involved 60 partner farmers selected purposively using a multi-stage sampling approach. Primary data were collected through interviews using structured questionnaires. The analytical method employed was farm analysis, which included calculations of fixed costs, variable costs, revenue, net income, and the R/C ratio. Results: The results show that the average total production cost incurred by farmers was Rp2,853,390 per planting season. Revenue from maize sales averaged Rp14,899,592, resulting in a net income of Rp12,046,202. The R/C ratio value of 5.20 indicates that the farming practice is highly efficient and profitable. Beyond economic benefits, the contract farming scheme also contributed to improved farmer access to production inputs, technical assistance, and guaranteed selling prices. Conclusion: The study concludes that contract farming is an effective alternative marketing strategy for increasing the income of smallholder farmers in rural areas. To support the sustainability of this program, policy backing from local governments, strengthening of farmer institutions, and enhanced transparency and fairness in contract agreements are essential. The findings of this study can serve as a reference for developing a more inclusive and sustainable agribusiness partnership model.